Systematics and paleobiology of a new articulated axial specimen referred to Iguanodon cf. galvensis (Ornithopoda, Iguanodontoidea). Issue 6 (10th December 2020) - Verdú, Francisco J.; Royo-Torres, Rafael; Cobos, Alberto; Alcalá, Luis
ABSTRACT: The early Barremian Iberian ornithopod Iguanodon galvensis was described for the first time in 2015. However, much of its anatomy, such as the axial skeleton in mature specimens, remains unknown. Here, the partially articulated presacral vertebrae and ribs belonging to a large adult ornithopod (DS-1 ornithopod) from the lower Barremian (Lower Cretaceous) that were found in Teruel Province (northeast of the Iberian Peninsula, Spain) are investigated by a systematic study and a phylogenetic analysis. The only cervical vertebra preserved is strongly opisthocoelus, as is typical of styracosternans. In fact, the phylogenetic analysis resolves DS-1 ornithopod as an hadrosauriform styracosternan. The assemblage also includes ten anterior-to-posterior dorsal vertebrae that strongly resemble those of the contemporary European iguanodontoid Iguanodon, particularly in having amphiplatyan and higher-than-long centra and dorsal neural spines two times the lateral height of their centra and slightly sigmoid in the posterior vertebrae. In addition, the dorsal centra are moderately compressed between the articular faces and lack a ventral keel, unlike the late Barremian type species I. bernissartensis but resembling the sympatric I. galvensis . For these reasons, DS-1 ornithopod is ascribed here as I. cf. galvensis . Moreover, this specimen has costovertebral ankyloses likely related to the specimen's maturity. Finally, the fossils of I. galvensis including those referred to it as DS-1 ornithopod, as well as evidence provided by bones and tracks in other places, indicate that the genus Iguanodon frequently occupied areas around rivers, lakes, estuaries, or lagoons.